BI 1015550 is a PDE4B Inhibitor and a Clinical Drug Candidate for the Oral Treatment of Idiopathic Pulmonary Fibrosis - Herrmann, Franziska Elena; Hesslinger, Christian; Wollin, Lutz; Nickolaus, Peter (Frontiers in Pharmacology, 2022)
Graphical Abstract